Analisis pengaruh online review pada booking.com terhadap keputusan wisatawan menginap di de vins sky hotel seminyak, bali - Silvia Sevtiani; Anak Agung Putri Sri; Ni Putu Ratna Sari (Jurnal Kepariwisataan dan Hospitalitas, 2020)
Abstract On the site for online review there are some elements that are often read, namely information about the object sought, products presented in the form of reviews, photos, places and facilities downloaded on the page which will influence the decision to stay at a hotel. The purpose of this study was to determine the effect of an online review market (general information, reviews, photos, location, and facilities) on the booking.com site on travelers' decisions to stay at De Vins Sky Hotel, Seminyak. To find out the most significant variable influencing tourist decisions to stay at De Vins Sky Hotel, Seminyak. The way to collect data is through observation, questionnaires and literature study. The research method used in this research is Descriptive Statistical Analysis with Likert scale calculation, and Inferential Statistical Analysis consisting of correlation analysis, Multiple Linear Analysis, Simultaneous Analysis (F Test), Partial Analysis (T test), Determination Analysis. The results showed that there was a positive and significant influence from the Online Review on Booking.com on travelers' decision to stay at De Vins Sky Hotel with an F value of 19.667> F table (3.94) and sig. 0,000 <0.05, which means that the effect simultaneously so if the X variable (Online Review) increases or influences in one unit, then the variable Y (Decision Overnight) will increase or be fulfilled. The conclusion in outline is that online review has a positive and significant effect on travelers' decision to stay at De Vins Sky hotel with the most significant sub-variable facilities. Keywords : Online Review, Booking.com, Decision to Stay.